2018
DOI: 10.1080/23802359.2018.1522982
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitogenome of the biocontroller fungusPurpureocilliumsp. (Ascomycota, Ophiocordycipitaceae, Hypocreales)

Abstract: The strain Purpureocillium sp. UdeA0106 is an antagonist of nematodes, fungi, and garden symphylans from crops with high economic importance in Colombia (Salazar 2013 ; Salazar et al. 2014 ; Cardona et al. 2014 ; Gallego et al. 2014 ) and is being studied to be proposed as new species. It was included on the 1000 fungal genomes project to elucidate its phylogenetic relationships with other fungi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
4
2
0
Order By: Relevance
“…Our results were supported by other studies which reported that fungicides decrease pathogen infections by stimulating the rhizosphere microbial community ( Zhou et al, 2020 ). The abundance levels of Proteobacteria, Actinobacteria, and Ascomycota were significantly high in T. controversa -infected plants that were coated with a fungicide when compared to the control plants ( Figure 4 ), and the above-mentioned findings were supported by the previous studies ( Newman et al, 2016 ; Cardona et al, 2018 ). Overall, we optimized the fungicide concentration to control dwarf bunt based on the signature of the microbial community.…”
Section: Discussionsupporting
confidence: 85%
“…Our results were supported by other studies which reported that fungicides decrease pathogen infections by stimulating the rhizosphere microbial community ( Zhou et al, 2020 ). The abundance levels of Proteobacteria, Actinobacteria, and Ascomycota were significantly high in T. controversa -infected plants that were coated with a fungicide when compared to the control plants ( Figure 4 ), and the above-mentioned findings were supported by the previous studies ( Newman et al, 2016 ; Cardona et al, 2018 ). Overall, we optimized the fungicide concentration to control dwarf bunt based on the signature of the microbial community.…”
Section: Discussionsupporting
confidence: 85%
“…Our results were supported by other studies which reported that fungicides decrease pathogen infections by stimulating the rhizosphere microbial community . The abundance levels of Proteobacteria, Actinobacteria, and Ascomycota were significantly high in T. controversa-infected plants that were coated with a fungicide when compared to the control plants (Figure 4), and the above-mentioned findings were supported by the previous studies (Newman et al, 2016;Cardona et al, 2018). Overall, we optimized the fungicide concentration to control dwarf bunt based on the signature of the microbial community.…”
Section: Discussionsupporting
confidence: 79%
“…A similar pattern of phylogeny branching was obtained for fungi of Ascomycota by Ghikas et al (2006), for selected Basidiomycota and Ascomycota by Aguileta et al (2016), for Pezizomycotina by Cardona et al (2018), and for Hypocreales by Wang et al (2017). Therefore, the combination of 14 mitochondrial gene set analyzed in this work may be a useful strategy for fungal taxa identi cation and phylogenetic analysis.…”
Section: Phylogenetic Analysessupporting
confidence: 82%
“…Phylogenetic analyses were performed using the 14 conserved mitochondrial genes of a database constructed with selected taxa from the Subphylum Pezizomycotina (Cardona et al 2018). In addition, three species of the Subphylum Saccharomycotina, as Candida albicans, Candida glabrata, and Wickerhamomyces canadensis were used as outgroups.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%